Numerical study of a steel sub-frame in fire - Santiago, Aldina (2008)
Steel-framed buildings are generally designed with "simple" shear-resisting connections, and lateral forces are resisted by vertical bracing and shear walls. When a beam is considered then the effects of the longitudinal restraints by the adjacent structure and the rotational restraint by the connections has to be taken into account. Because of structural interaction, the beam behaviour at elevated temperature is rather complex.